A methodology for assessing public health risk associated with groundwater nitrate contamination: a case study in an agricultural setting (southern Spain) - Chica-Olmo, Mario (2016)
Groundwater nitrate contamination from agriculture is of paramount environmental interest. A continuous consumption of polluted water as drinking water or for culinary purposes is by no means a minor hazard for people’s health that must be studied. This research presents a new methodology for the spatial analysis of health risk rate from intake of nitrate-polluted groundwater. The method is illustrated through its application to a water quality sampling campaign performed in the south of Spain in 2003. The probability risk model used by the US Environmental Protection Agency has been applied, considering a residential intake framework and three representative population age groups (10, 40 and 65years).The method was based upon coupling Monte Carlo simulations and geostatistics, which allowed mapping of the health risk coefficient (RC). The maps obtained were interpreted in the framework of water resources management and user’s health protection (municipalities). The results showed waterborne health risk caused by nitrate-polluted water is moderately low for the region. The observed risk was larger for the elderly and children, although no significant differences were found among the three age groups (RC average values of 95th percentile for age of 0.37, 0.33 and 0.37, respectively). Significant risk values of RC>1 were obtained for 10% of the surface in the NW site of the study area, where the municipalities with the highest contamination thresholds are located (agricultural activity). Nitrate concentration and intake rate stood out as the main explanatory variables of the RC.